Profesor Dato' Dr. Hj. Raja Abdullah Raja Yaacob / Muhamad Fahmi Shamsi and Nurul Syuhaida Azmi - Shamsi, Muhamad Fahmi; Azmi, Nurul Syuhaida (2011)
Raja Abdullah Raja Yaacob is a pioneer of the Faculty of Information Management, UiTM both as a student as well as a lecturer. He was responsible in raising the status of the Faculty to its present and has placed it to a high level as it is recognized worldwide. He started from the bottom to achieve success today. He entrusted his position as dean of the Faculty of Information Management for almost 8 years since 1995 until 2001. During that time he has managed to change, to formulate and develop a variety of activities and introduced new programs in the field of Information Management. In 2001, the faculty has increased the number of students from 115 to 4000 and the number of lecturers from 13 to 120. In addition, he still active in the field of writing. He is also involved actively in introducing and promoting library and information management to the public. In 2001, he was conferred the award of Dato' Paduka Mahkota Perak (DPMP) which carries the title of Dato'. For the future, he plans to be involved in introducing several programs, such as Health Information Management, Legal Information Management, Islamic Information, Entrepreneur Information etc. He also advised the students to read all sources of information and to gain knowledge and fluency in English.